Labellisation UNESCO… et après ? - François H. Courvoisier (Presses de l'Université du Québec, 2021)
Based on a literature review and on half-structured interviews with officials from two Swiss sites, the watchmaking urbanism of La Chaux-de-Fonds and Le Locle, as well as the terraced vineyards of Lavaux, this research examines and analyzes the impact of a UNESCO World Heritage listing of both sites ten years after their inscription. It shows, on the one hand, that the tourism impact is limited in terms of increased attendance and that the quantitative indicators are lacking. On the other hand, the UNESCO label gives more pride to the inhabitants and stakeholders, more visibility to the sites concerned, and stimulates perspectives for territorial development projects.